2020
DOI: 10.3390/coatings10121159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exposure Conditions on the Interfacial Bond Properties of SS400 Plate Coated with Various Epoxy Resins

Abstract: This study aims to investigate the effects of different exposure conditions on the interfacial bond between steel plates and epoxy resin coatings at early ages. Test variables include the epoxy resin types, exposure conditions, exposure periods, and coating equipment. The selected epoxy resins were applied to prepared steel plates and cured at each exposure condition for 7, 28, 56, or 91 days, and the pull-off bond strength and coating thickness were measured. Scanning electron microscopy (SEM) images were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Notably, D1 exhibited the highest variation with an S.D. of 123 µm, which was unexpected considering that D1 was initially anticipated to have a stable thickness compared with other methods based on previous findings [10,21,22]. The mean bond strengths of D1, D2, and D3 were 1.87, 1.70, and 1.58 MPa, respectively, and no significant difference between the groups was observed at the 0.05 significance level.…”
Section: Effect Of the Coating Methods On The Measured Thickness And ...mentioning
confidence: 72%
See 2 more Smart Citations
“…Notably, D1 exhibited the highest variation with an S.D. of 123 µm, which was unexpected considering that D1 was initially anticipated to have a stable thickness compared with other methods based on previous findings [10,21,22]. The mean bond strengths of D1, D2, and D3 were 1.87, 1.70, and 1.58 MPa, respectively, and no significant difference between the groups was observed at the 0.05 significance level.…”
Section: Effect Of the Coating Methods On The Measured Thickness And ...mentioning
confidence: 72%
“…Nonetheless, it was anticipated that the bond strength measured under laboratory conditions using tap water would demonstrate a higher strength value compared to the other conditions. This expectation was rooted in our prior research, which indicated that the pull-off bond strength measured under consistent temperature and humidity conditions consistently yielded higher results when contrasted with measurements taken under real sea (RS) conditions [10,21,22]. The exact causes behind this notable onsite variability remain undetermined, but they could be linked to uncontrolled variables and unforeseen factors, including temperature fluctuations, humidity levels, tidal effects, and the presence of marine organisms.…”
Section: Measured Pull-off Bond Strengthmentioning
confidence: 87%
See 1 more Smart Citation
“…A carbon steel plate with a size of 150 mm × 50 mm × 4 mm was used as the base material to prepare the specimen. There are many coating methods, but the commonly used method in this field is to use a traditional roller to coat the surface of the substrate alone [22]. Due to manual mixing and roller coating, the coating may be thin on the four sides of the substrate or uneven in certain areas.…”
Section: Preparation Of Test Specimenmentioning
confidence: 99%
“…At the same time, good interfacial adhesion between the coating and the electrode is necessary for the coating to play a full role. Many studies have been conducted on adhesion changes and methods to improve adhesion [24][25][26]. The coating and substrate are combined due to mechanical bite, physical adsorption with van der Waals force as the prominent role and chemical adsorption with chemical bonds as the leading role.…”
Section: Introductionmentioning
confidence: 99%